Analyzing the Potential Antioxidative Effects of Omega-369 in Preventing Acetaminophen-Induced Liver Damage - Hashim Mohammed, Yousif; Hassan, Ali Faris (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2023)
Background: As acetaminophen (APAP) toxicity has become more common in many countries, related cases of poisoning, whether deliberate or unintentional, have been identified as a key contributor to acute liver failure. Aime: To discover if omega-369 fatty acids could protect the liver of male mice from the effects of acetamiophen. Methods: Thirty-five albino male mice were randomly assigned to one of five groups. Group 1 served as the "negative control" and received a single intraperitoneal injection (10 ml/kg) of normal saline on the eleventh day of the test following ten days of receiving liquid paraffin orally at a dose of 10 ml/kg. The liquid paraffin was given to group 2 "positive control". Group 3 received Omega 369 (50 mg/kg). Group 4 received Omega 369 (100 mg/kg). Group 5 received N-acetylcysteine (100 mg/kg). The mice were given Omega-369, N-acetylcysteine, and liquid paraffin via oral gavage for 10 days. Results: Group 2 had significantly lower levels of glutathione peroxidase (GP-X) and superoxide dismutase (SOD) than group 1, but significantly greater levels of malondialdehyde (MDA). GP-X and SOD levels were significantly higher in mice given the doses of omega-369, and N-acetylcysteine prior to acetaminophen administration, whereas MDA levels were significantly lower in groups 3, 4, and 5 when compared with group 2. Conclusion: Omega-369 fatty acids, when taken orally, exhibit antioxidative effects and may reduce the risk of acetaminophen-induced liver injury.